Mouse Platelet Ral GTPases Control P-Selectin Surface Expression, Regulating Platelet–Leukocyte Interaction. Issue 4 (April 2018) - Wersäll, Andreas; Williams, Chris M.; Brown, Edward; Iannitti, Tommaso; Williams, Neil; Poole, Alastair W.
Abstract : Objective—: RalA and RalB GTPases are important regulators of cell growth, cancer metastasis, and granule secretion. The purpose of this study was to determine the role of Ral GTPases in platelets with the use of platelet-specific gene-knockout mouse models. Approach and Results—: This study shows that platelets from double knockout mice, in which both GTPases have been deleted, show markedly diminished (≈85% reduction) P-selectin translocation to the surface membrane, suggesting a critical role in α-granule secretion. Surprisingly, however, there were only minor effects on stimulated release of soluble α- and δ-granule content, with no alteration in granule count, morphology, or content. In addition, their expression was not essential for platelet aggregation or thrombus formation. However, absence of surface P-selectin caused a marked reduction (≈70%) in platelet–leukocyte interactions in blood from RalAB double knockout mice, suggesting a role for platelet Rals in platelet-mediated inflammation. Conclusions—: Platelet Ral GTPases primarily control P-selectin surface expression, in turn regulating platelet–leukocyte interaction. Ral GTPases could therefore be important novel targets for the selective control of platelet-mediated immune cell recruitment and inflammatory disease. Abstract : Supplemental Digital Content is available in the text.